Wild ride [compact disc, unabridged] - Crusie, Jennifer (Brilliance Audio, 2009)
When Mary Alice Brannigan comes home to Ohio to restore the Dreamland amusement park, she doesn't expect to fall in love with a clown. Nor does she expect to find that she's the newest recruit in the Guardia, an elite team of demon fighters formed centuries before to guard the five Untouchables, the most powerful demons in the history of the world, now imprisoned right there in Dreamland.